PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP ENVIRONMENTAL DISCLOSURE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Yulisa Aji Pradesti (AKT 16 UMY 571, 2015)
This research aims to examine the factors that influence of the environmental disclosure. Measurement of environmental disclosure in a company of this research used the Global Reporting Initiative (GRI). The independent variable in this research is the proportion of independent board, demain commissioner of educational background, the number of board meetings, and profitability, the size of the company, leverage. The population of this research is manufacturing companies that listed in Indonesia Stock Exchange (IDX) in 2012-2014. The selection of the sample of this research using purposive sampling method, that is the company who published the annual report and financial report. Based on purposive sampling method, the number of samples obtained are 162 sample firms. The analysis of this study uses multiple regression analysis using SPSS15.0. The results of this study indicate that the demain commissioner of educational background and size of the company has positive influence on environmental disclosure. The proportion of independent board, the number of board meetings, profitability, and leverage does not affect the environmental disclosure. Keywords: The proportion of independent board, demain commissioner of educational background, the number of board meetings, profitability, size of the company, and leverage, environmental disclosure